Theatrical innovation in contemporary circus: Juggling rings into birds - Eigtved, Michael (Peripeti, 2025)
The article describes and discusses the way circus artists were educated and worked artistically with their discipline on the no longer functioning Danish circus school Academy of Modern Circus (AMoC). Setting off from the idea of “theatrical innovation”, the work of Czech juggler, Filip Zaradnický is pursued to investigate how a combination of a semiotic and phenomenological approach may be useful to analyse the development of the act as well as the experience of it.